Influência da quantidade de dentifrício e concentração de fluoreto na retenção intrabucal de fluoreto em crianças - Moraes, Felipe Ricardo Nunes de [UNESP] (2017)
This study evaluated fluoride (F-) concentrations in saliva of children after brushing with dentifrices containing different F concentrations (0, 550 and 1100 ppm F) in different quantities (0.1, 0.3 and 0.5 g). Volunteers (n=24, 8-10 years old) were randomly assigned into 9 experimental groups, according to the possible combinations of dentifrice type and amount, following a double-blind, crossover protocol. They were instructed to brush their teeth with a placebo dentifrice during one week (wash out). On the 7th day, stimulated saliva was collected prior to tooth brushing (baseline) and at 5, 15, 30, 60 and 120 min after tooth brushing. Saliva samples were then centrifuged and the supernatants used for F- analysis after buffering with TISAB III (total ionic strength adjustment buffer). The area under the curve (AUC) for salivary F- clearance was calculated using the individual points (trapezoidal rule). Data of salivary flow rate, F- concentrations at each collection point and AUC were submitted to two-way, repeated-measures ANOVA, followed by the Student-Newman-Keuls test (p<0.05). A marked peak in salivary F- concentrations was seen 5 min after brushing, decreasing exponentially afterwards. A clear dose-response relationship was seen between F concentration and amount of dentifrice and the mean AUC of salivary F concentrations (p<0.001). Tooth brushing with 0.3 and 0.5 g of the low-fluoride dentifrices led to significantly higher AUC than the conventional dentifrices using 0.1 g. It can be concluded that brushing with a 0.3 g of a low-fluoride dentifrice delivers more fluoride in saliva in comparison with a 0.1 g of a conventional dentifrice